Effects of body weight loss on serum progesterone concentrations of non-lactating dairy cows - Rodrigues, R. O. [UNESP]; Trevisanuto, C. [UNESP]; Cooke, Reinaldo Fernandes [UNESP]; Vasconcelos, José Luiz Moraes [UNESP] (Elsevier B.V., 2011)
The objective was to evaluate serum concentrations of nonesterified fatty acids (NEFA), cortisol, insulin, and progesterone (P4) of dairy cows maintaining or mobilizing body weight (BW). Eleven non-lactating, non-pregnant, and ovariectomized Gir X Holstein cows were stratified by BW and body condition score (BCS), and randomly assigned to: 1) BW loss (six cows; LOSS) and 2:1 BW maintenance (five cows; MAINT). Treatments were achieved through a grazing schedule using three pastures. From Days -7 to 1 of the study, all cows were maintained in Pasture A (12 kg of dry matter/cow daily). From Days 2 to 30, LOSS cows were maintained in Pasture B (less than 1.0 kg of dry matter/cow daily), whereas MAINT cows were maintained in Pasture C (12 kg of dry matter/cow daily). However, from Days 3 to 30 of the study, cows from both treatments were regrouped daily into Pasture A from 0600 to 1200 h to allow LOSS cows to consume, on average, 4.5 kg/d of forage dry matter. on Day -66 of the study, all cows received an intravaginal drug releasing device containing 1.9 g of P4 (replaced every 14 d and removed on Day 3). Cow BW and BCS were assessed on Day 0 and 30 and blood samples were collected daily from Days 0 to 30 at 0600 and 1200 h. Changes in BW and BCS were greater (P <= 0.05) in LOSS cows compared to MAINT cows. Within samples collected at 0600 h, serum NEFA concentrations were often greater (P < 0.05) in LOSS cows compared to MAINT after Day 14. Serum P4 concentrations were greater (P < 0.05) on Days 21 and 22, and tended (P < 0.10) to be greater on Days 16, 23, and 24 of the study in LOSS cows compared to MAINT. In conclusion, BW loss was associated with increased circulating concentrations of P4 in non-lactating ovariectomized dairy cows; this was mainly attributed to fat mobilization and consequent release of P4 stored in adipose tissues. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Adipose tissues; Weight loss; Body condition score; Dairy cows; Progesterone